The Position of Interns In Labor Law: Rights And Obligations - Titaley, Paulus (Journal of Law, Politic and Humanities, 2025)
The increasing prevalence of internship programs in Indonesia has led to renewed focus on the legal status, rights, and obligations of interns within the national labor law framework. This study employs a normative juridical method using statute and conceptual approaches to analyze the regulatory landscape governing internships. Interns occupy a unique legal position that distinguishes them from formal workers or employees, especially concerning their contractual arrangements, remuneration, and access to legal protections. Although internship programs are intended to equip participants with workplace skills and experience, they may also give rise to legal ambiguities and risks of exploitation due to unclear employment status and the absence of enforceable labor rights. This research emphasizes the importance of clear regulatory frameworks and binding agreements to ensure that interns receive appropriate training, protection, and recognition while fulfilling their obligations within host organizations. Strengthening legal norms can provide better safeguards and legal certainty for all parties involved.